2012
DOI: 10.1111/j.1744-7348.2012.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundant genetic diversity of the wild rice Zizania latifolia in central China revealed by microsatellites

Abstract: Wild rice Zizania latifolia is a perennial emergent aquatic plant widely distributed across China. Wild populations of Z. latifolia are important to aquatic ecosystems and are valuable genetic resources for breeding. However, they have been faced with significant habitat losses in recent decades. For 10 nuclear microsatellites, high levels of genetic diversity (HE = 0.572–0.636) were found across seven surveyed populations from central China. The main factors responsible for that were its long life history and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…For a species that is endemic in wetlands of the Yangtze River, M. lutarioriparius exhibited a higher level of genetic variation across its distribution range (H E = 0.682-0.786; A r = 4.74-8.06; Tables 1 and S1) compared to Myricaria laxiflora and Zizania latifolia within the same habitat and distributing range (Liu et al, 2006;Chen et al, 2012). However, the genetic diversity was comparable with the riparian pioneer tree species Populus nigra along the Drôme River (France), which had similar dispersal mechanisms (Imbert & Lef evre, 2003).…”
Section: Genetic Diversity and Adaptationmentioning
confidence: 99%
“…For a species that is endemic in wetlands of the Yangtze River, M. lutarioriparius exhibited a higher level of genetic variation across its distribution range (H E = 0.682-0.786; A r = 4.74-8.06; Tables 1 and S1) compared to Myricaria laxiflora and Zizania latifolia within the same habitat and distributing range (Liu et al, 2006;Chen et al, 2012). However, the genetic diversity was comparable with the riparian pioneer tree species Populus nigra along the Drôme River (France), which had similar dispersal mechanisms (Imbert & Lef evre, 2003).…”
Section: Genetic Diversity and Adaptationmentioning
confidence: 99%
“…But this study and Fan et al (2016) both showed that Z. latifolia in the plain has exhibited inbreeding. On the contrary, Z. latifolia populations from the Yangtze River showed predominant outcrossing reproductive system (F IS = −0.200-0.019; Chen et al, 2012a). The different results could be ascribed to the habitat types: most Z. latifolia populations in the Sanjiang Plain occur in the sides of ponds and streams, which easily lead to mating events among close relatives or intra-clones; while Z. latifolia from the Yangtze River grows along the littorals of lakes and forms large populations (Chen et al, 2012a), and this makes the populations stand a good chance to receive more migrant pollen and act as outcrossing.…”
Section: Clonal Diversity and Genetic Variationmentioning
confidence: 99%
“…In the present study, Z. latifolia from the Sanjiang Plain appeared to possess low intra-population microsatellite variation (n a = 2.3, H E = 0.328) compared to Z. texana from Texas in America (n a = 11.7, H E = 0.662, Richards et al, 2007; n a = 4.4-6.3, H E = 0.53-0.65, Wilson et al, 2017) and Z. latifolia from the Yangtze River in central China (n a = 5.0, H E = 0.610; Chen et al, 2012a). A lower level of genetic variation (H E = 0.156 based on SRAP markers) was found in nine Z. latifolia populations in the same area (Fan et al, 2016).…”
Section: Clonal Diversity and Genetic Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other molecular markers, simple sequence repeat (SSR) markers have numerous merits, including co-dominance, high reproducibility, a relatively high level of polymorphisms, and are plentiful in the genome ( Liao et al, 2013 ). SSR markers have been successfully applied to estimate the genetic diversity of other aquatic plants such as Sparganium emersum ( Pollux et al, 2007 ), Zostera marina ( Reusch, Stam & Olsen, 2000 ; Talbot et al, 2016 ), Sagittaria natans ( Yue et al, 2011 ), Zizania latifolia ( Chen et al, 2012 , 2017 ), Nymphoides peltata ( Liao et al, 2013 ), Isoetes hypsophila ( Li et al, 2013 ), Ruppia cirrhosa ( Martínez-Garrido, González-Wangüemert & Serrão, 2014 ), Nuphar submersa ( Shiga et al, 2017 ), and Ottelia acuminata ( Zhai, Yin & Yang, 2018 ). Here, we used 12 microsatellite loci to detect and estimate the genetic variation of B. schreberi in China.…”
Section: Introductionmentioning
confidence: 99%